1976
DOI: 10.2190/a692-9epd-l2ke-t192
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Death in Relation to Powerlessness and form of Personal Religion

Abstract: Research on religion and death perspectives has resulted in many contradictory findings. It was hypothesized that one reason for this situation stems from the treatment of both domains as unidimensional. The present study examined the pattern of relationships among multidimensional measures of religion and death outlooks. The possible involvement of powerlessness as a confounding factor was also evaluated. Utilizing religious respondents four forms of personal religion and nine death perspectives were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The lack of a relationship between well-being and religiousness in the terminally ill group may be explained by fhe complexity of factors that contribute to well-being. For example, powerlessness (Minton & Spilka, 1976) and congruency between lifestyle and religiousness (Shaver, Lenauer, & Sadd, 1980) influence the relationship between well-being and religion. Others described this relationship as weak but nevertheless significant (Carey, 1974;Hadaway, 1978;Spreitzer & Snyder, 1974.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a relationship between well-being and religiousness in the terminally ill group may be explained by fhe complexity of factors that contribute to well-being. For example, powerlessness (Minton & Spilka, 1976) and congruency between lifestyle and religiousness (Shaver, Lenauer, & Sadd, 1980) influence the relationship between well-being and religion. Others described this relationship as weak but nevertheless significant (Carey, 1974;Hadaway, 1978;Spreitzer & Snyder, 1974.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, empirical research on death attitudes have focused primarily on death anxiety and its wide reaching effects on psychological functioning. For instance, death anxiety is linked to emotions such as guilt, motivation such as powerlessness (Minton & Spilka, 1976), and personality traits such as neuroticism (Lee & Surething, in press). The core of one's self is also adversely affected by death anxiety such that it is associated with lower levels of self-efficacy (Tang, Wu, & Yan, 2002), self-esteem (Cotter, 2003), and self-control (Galliot, Schmeichel, & Baumeister, 2006).…”
Section: Attitudes Toward Death: Death Anxiety and Death Fascinationmentioning
confidence: 99%
“…Finally, and most important for our line of reasoning, there are several studies showing that various measures of fear of death are negatively correlated with intrinsic and positively correlated with extrinsic religious orientation (e.g., Bolt, 1977;Minton & Spilka, 1976;Spilka et al, 1977; for review, see Donahue, 1985 2 ). Genia (1996) concluded that intrinsic religiousness can be seen as a strong predictor of psychospiritual health and that intrinsic believers' sense of a personal relationship with God may make them less vulnerable to existential angst.…”
Section: Intrinsic Versus Extrinsic Religious Orientationmentioning
confidence: 99%